Evaluation of cytotoxic effects of amitriptyline on ovarian cancer cells - Dehghani, Atefe; Tabaku, Afrim; Kamalzadeh, Shokouh (Journal of Biological Studies, 2022)
Many studies have shown that antidepressants can have anticancer effects; however, the anti-cancer effects of the antidepressant amitriptyline on ovarian cancer cells are unclear. Accordingly, the present study investigated the cytotoxic effects of amitriptyline on ovarian cancer cells in vitro. In this experimental-laboratory study, ovarian cancer (A2780) cells were divided into control (untreated) group and groups treated with 78.125, 156.25, 312.5, 625, 1250 and 2500 μg/ml of amitriptyline. Cell viability was measured using the MTT assay method 24 and 48 hours after treatment. Data was analyzed using a one-way analysis of variance. Ovarian cancer cell viability significantly reduced after treatment with 78.125, 156.25, 312.5, 625, 1250, and 2500 μg/ml after 24 and 48 hours (p < 0.001). IC50 the drug was 1144 and 1071 for 24 and 48 hours, respectively. The findings of this study indicate that amitriptyline has cytotoxic effects on ovarian cancer cells.